Wheat Argonaute 5 Functions in Aphid–Plant Interaction - Sibisi, Phumzile; Venter, Eduard (Frontiers in Plant Science, 2020)
Aphids feeding on plants experience similar responses to pathogens due to the prolonged and intimate contact with the plant. Diuraphis noxia is an economically important aphid pests on wheat that exhibit such an interaction. Several microRNA was identified that regulate the early interaction between D. noxia and resistant wheat. Here we extended our knowledge of regulated miRNA in wheat after infestation. This led to the discovery of a differentially regulated Argonaute 5 protein (TaAGO5). A phylogenetic analysis grouped the identified TaAGO5 together with two splice variants from the wheat genome. TaAGO5 lacked the first two domains found in AGO proteins and only half of the PAZ domain is present. None of the conserved amino acids for the PAZ domain occur in TaAGO5. There is also a duplication event inserted into the PIWI domain that is not found in the two splice variants. Functional characterisation revealed that TaAGO5 is crucial in regulating the response to infestation by D. noxia. This regulation was similar to that observed in Nicotiana tabacum when exposed to larvae oral secretions. This hints at a similar response in wheat after aphid feeding to plants experiencing arthropod herbivory. Additionally, TaAGO5 is regulated by viruses and displayed a response to the Barley mosaic virus (BMV) used in the functional characterisation. These observations extends our knowledge on the roles of AGO proteins in plant resistance.